Numerical investigation of Kingfisher’s wing under multi-phase flight for micro-aerial-vehicle - Abas, Mohd Firdaus (2019)
Realizing an all-weather Micro-Aerial-Vehicle (MAV) has been this research’s ultimate purpose. This research focuses on the originality of Kingfisher- inspired rigid and flexible wing designs and flapping patterns, and the novelty of multi-phase flapping flight. Numerical investigations have been conducted at 4.4 m/s, 6.6 m/s, and 8.8 m/s flight velocities, 11 Hz, 16 Hz, and 21 Hz flapping frequencies, and before, during, and after multi-phase impact with rain environment flight conditions. An experimental validation has been conducted using 3-D printed wing model under Particle Image Velocimetry (PIV) examination. The numerical investigations have been designed, mesh- constructed, and simulated using SolidWorks, Pointwise, and ANSYS Fluent software, respectively. For the main Kingfisher-inspired flapping rigid wing model, both coefficient of lift (CL) and thrust force values under normal (ambient air) environment decreases with increased in flight velocity but increases with increased in flapping frequency, in a similar fashion. The main flapping rigid wing model at flight condition of 4.4 m/s flight velocity, 21 Hz flapping frequency, and 12° angle-of-attack shows the most optimal flight performance with exceptional overall aerodynamic characteristics. The flapping flexible wing model’s resulted CL value is 12.573% higher than the flapping rigid wing model under Single-phase flight condition. Furthermore, the flapping flexible wing model generates a staggering 81.064% higher thrust force with 41.030% lower coefficient of pressure (CP) value than the flapping rigid wing model under the same flight condition. Under Multi-phase flight condition through simulated rain environment, the flapping flexible wing produces 14.726% higher CL value and generates a staggering 82.527% higher thrust force with 62.770% lower CP value than the flapping rigid wing at point of rain impact. This in turn enables the flapping flexible wing to adapt to the new simulated rain environment 24 times faster than the flapping rigid wing, which only took 0.0048 second. After rain impact, the flapping flexible wing produces 15.406% higher CL value and generates a staggering 83.516% higher thrust force with 34.555% lower CP value than the flapping rigid wing under said simulated rain environment. As a conclusion, the flexible wing model counterpart shows greater aerodynamic performance under every investigated flight conditions as compared to the rigid wing model.